1999
DOI: 10.1046/j.1440-1681.1999.03113.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevation Of Striatal Interleukin‐6 and Serum Corticosterone Contents In Mptp‐Treated Mice

Abstract: 1. Changes in the content of striatal interleukins (IL-1 beta and IL-6) and serum corticosterone in relation to deterioration of the dopaminergic system induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP; a dopaminergic neurotoxin; 20 mg/kg i.p., four administrations/12 h) in C57BL/6J mice were investigated. 2. Striatal dopamine, IL-1 beta, IL-6 and serum corticosterone were measured on days 1 and 7 post-MPTP. 3. Dopamine depletion was more severe on day 7 than on day 1 post-treatment. 4. Increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Genetic ablation of either Tnf-α or both its receptors, Tnfrsf1 and Tnfrsf2 is reported to confer protection against MPTP toxicity as measured by attenuation of dopamine depletion in the striatum (Sriram et al, 2002,Ferger et al, 2004,Sriram et al, 2006a,Sriram et al, 2006b, although neither genetic ablation nor pharmacological manipulation of Tnf-α prevents neuronal loss in the SNpc (Rousselet et al, 2002,Ferger et al, 2004,Leng et al, 2005. Therefore, our results are consistent with the view that although Tnf-α may influence dopaminergic terminals in the striatum, it cannot explain genetic resistance to MPTP as measured by loss of TH-positive neurons in the SNpc.Our results for Il-6 mRNA levels also support prior studies showing that MPTP increases striatal Il-6 levels (Kaku et al, 1999,Hebert et al, 2003. Additionally, we show that MPTP elicits higher levels of Il-6 mRNA in SWR compared to C57BL/6J mice, suggesting that this cytokine may contribute to MPTP resistance.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Genetic ablation of either Tnf-α or both its receptors, Tnfrsf1 and Tnfrsf2 is reported to confer protection against MPTP toxicity as measured by attenuation of dopamine depletion in the striatum (Sriram et al, 2002,Ferger et al, 2004,Sriram et al, 2006a,Sriram et al, 2006b, although neither genetic ablation nor pharmacological manipulation of Tnf-α prevents neuronal loss in the SNpc (Rousselet et al, 2002,Ferger et al, 2004,Leng et al, 2005. Therefore, our results are consistent with the view that although Tnf-α may influence dopaminergic terminals in the striatum, it cannot explain genetic resistance to MPTP as measured by loss of TH-positive neurons in the SNpc.Our results for Il-6 mRNA levels also support prior studies showing that MPTP increases striatal Il-6 levels (Kaku et al, 1999,Hebert et al, 2003. Additionally, we show that MPTP elicits higher levels of Il-6 mRNA in SWR compared to C57BL/6J mice, suggesting that this cytokine may contribute to MPTP resistance.…”
supporting
confidence: 90%
“…Differences between strains were analyzed by two-way ANOVA followed by Bonferroni's post-test. Prior studies have reported increases in Tnf-α and Il-6 using the MPTP model (Kaku et al, 1999,Hebert et al, 2003, and mice deficient in Tnf-α receptors or Il-6 have altered responsiveness to MPTP (Bolin et al, 2002,Sriram et al, 2002,Cardenas and Bolin, 2003,Ferger et al, 2004,Leng et al, 2005. Therefore, we examined levels of Tnf-α and Il-6 mRNA in both sensitive and resistant strains of mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This occurs early in neuronal degeneration, starting at the extending fibres, such as the dendrite which extends into the SN reticulata (Sugama et al, 2003). Hence, activated glial cells release detrimental compounds such as, interleukin (IL)-1β, IL-6, tumor necrosis factor-α (TNF-α) and interferon γ (IFN-γ), which may act by stimulating inducible nitric oxide synthase (iNOS), or which may exert a more direct deleterious effect on DAergic neurons by activating receptors that contain intracytoplasmic death domains involved in apoptosis (Kataoka et al, 1997;Mogi et al, 1998;Kaku et al, 1999;KurkowskaJastrzębska et al, 1999a,b;Knott et al, 2000;Iravani et al, 2002;Teismann et al, 2003;Przybyłkowski et al, 2004;de Meira Santos Lima et al, 2006). Microglia can also induce neuritic beading (Takeuchi et al, 2005) or synaptic stripping along dendrites (Schiefer et al, 1999) leading to synaptic disconnection and loss of trophic support and cell death (Isacson et al, 1985;Jiang et al, 2006).…”
Section: Studymentioning
confidence: 99%
“…In the MPTP (1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine) model of PD, inflammatory reactions have been determined [9][10][11] and elevated pro-inflammatory cytokines have been found [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%